Auger recombination and leakage in InGaN/GaN quantum well LEDs - Roemer, Friedhard; Deppner, Marcus; Range, Christian; Witzigmann, Bernd (Proceedings of SPIE - The International Society for Optical Engineering, 2014)
The efficiency of blue InGaN/GaN light emitting diodes (LEDs) for solid state lighting has been strongly increased in the past years. The decay of the internal quantum efficiency at current densities above 100 Acm-2 remains, though. This effect is known as droop and effectively limits the maximum current density. The physical mechanisms behind the droop are not yet fully understood. Theories for the origin of the droop include the Auger recombination process and direct carrier leakage. In this context we present an analysis of the contribution of these effects to the droop by means of physics based simulation. In contrast to lumped simulation models the physical simulation model presented in this work enables the exact matching of the internal quantum efficiency (IQE) characteristics by including the geometry, doping, and mole fraction profiles. The analysis presented in this work uses the IQE data of a fabricated blue single quantum well LED. Fitting this IQE curve with the physics based simulation enables the estimation of limits for the Auger coefficients as well as the contribution of the direct carrier leakage. Including Auger assisted carrier leakage facilitates fitting the IQE with reduced Auger coefficients closing the gap to atomistic simulations. © 2014 SPIE.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Auger recombination; droop; gallium nitride; internal quantum efficiency; leakage; light emitting diode; simulation